ANALISIS PENGARUH TINGKAT SUKU BUNGA DAN PMDN TERHADAP PERTUMBUHAN EKONOMI DI KALIMATAN BARAT - B01108004, Riko (Jurnal Pembangunan dan Pemerataan, 2013)
This study titled analasis economic growth in West Kalimantan, the goal is to determine how much influence the interest rates and PMDN on economic growth. This study using correlative and regression analysis using eviews program. Correlative methods used to examine the relationship variable investments, interest rates, money supply, inflation and economic growth, while the analysis of multiple variables are used to determine the independent variables (investment, interest rates, money supply, and inflation) to the dependent variable (economic growth). The data used are secondary data quarterly period 2002.kuartal 1-2010. Quarter 4 of the Central Bureau of Statistics and Bank Indonesia. The results showed that the correlation (R2) between the variable investments, interest rates, money supply, and inflation has a very strong connection to economic growth, and the F-test conducted between the variables have an impact investing, interest rates, money supply, and inflation to economic growth. While the t test, variable interest rates, money supply, and inflation significantly affect economic growth, but investments are not significantly influence economic growth. Based on the classic assumption test found that the estimates of the regression model containing positive autocorrelation, containing muktikolinearitas, and contains no heterocedastisity.Keywords:EconomicGrowth, PMDN and InterestRates